(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This thesis discusses the novel and historical genre, as well as the introduction of the novel genre into Uzbek litereature. It analyzes historical historical novels crated in national novel writing and historical genre novel written by Omon Mukhtar. The research scientifically reveals Omon Mukhtar’s style used in novel writing and his contributionto the novel genre.